An Adolescent Patient With Idiopathic Pulmonary Arterial Hypertension Weaned Off Intravenous Epoprostenol Following Treatment With Selexipag: A Case Report - Chida-Nagai, Ayako; Tsujioka, Takao; Sasaki, Daisuke; Izumi, Gaku; Yamazawa, Hirokuni; Takeda, Atsuhito (Frontiers in Pediatrics, 2022)
Idiopathic pulmonary arterial hypertension (PAH) is a rare, progressive disease affecting the pulmonary arteries. Epoprostenol, a synthetic prostaglandin analogue, is the most potent pharmacological treatment modality used in patients with PAH. However, it requires continuous intravenous infusion, which negatively impacts the patient’s quality of life and frequently results in complications, such as catheter-related bloodstream infection. We weaned an adolescent female patient off epoprostenol by gradually introducing oral selexipag over a sustained period, following many years of continuous intravenous epoprostenol use alone. Oral selexipag might have an efficacy comparable to epoprostenol in young patients with PAH.